Use of Sodium Alginate Biopolymer as an Extracting Agent of Methylene Blue in the Polymer-Enhanced Ultrafiltration Technique - Sanchez-Poblete, J; Santander-Meyer, R; Oyarce-Riveros, E (John Wiley and Sons Inc, 2021)
In this study, the removal of methylene blue (MB) cationic dye from an aqueous solution was investigated using the polymer-enhanced ultrafiltration (PEUF) technique with sodium alginate (SA) as an extracting soluble polymer, in combination with an ultrafiltration membrane of regenerated cellulose with a 10 kDa molar mass cut-off. SA was characterized via Fourier-transform infrared spectroscopy and thermogravimetric analysis. For ultrafiltration studies, the washing method was used to evaluate various experimental variables, such as the pH, SA dose and initial MB concentration, and adsorption isotherms to identify the optimal adsorption conditions. Finally, the regeneration of the SA polymer was evaluated in five consecutive cycles of adsorption–desorption of MB. In the obtained characterization results, the structural composition of SA and the characteristic thermal stability of the polymer were verified. The PEUF results demonstrated that a retention capacity of 98% of the MB was realized at pH 8.0 using 0.025 g of SA at an initial optimal MB concentration of 50 mg L−1. It is possible to observe that the Freundlich model better explain the interaction between the dye and the polymer surface. According to the results is demonstrated the regeneration capacity of the polymer and its subsequent reuse. © 2021 Wiley Periodicals LLC.